Melatonin prevents deterioration of erectile function in streptozotocin-induced diabetic rats via sirtuin-1 expression - ŞEKERCİ, ÇAĞRI AKIN; ŞENER, GÖKSEL; ŞENER, TARIK EMRE; TANIDIR, YILÖREN (WILEY, 2020)
A review of the literature indicated that sirtuin-1 expression, a regulator of nitric oxide bioavailability in erectile dysfunction (ED) after melatonin therapy, has not yet been investigated. The objective of this study was to evaluate the protective effects of melatonin for erectile function with sirtuin-1 protein expression in type 1 diabetic rat models. Fifty male Sprague Dawley rats were placed into five groups. Except for those in the control group (C), each animal received a single dose (60 mg/kg) of streptozotocin to induce diabetes. The animals were placed into the diabetes (D) group, insulin (I) group (6 U/kg/day), melatonin (Mel) group (10 mg kg(-1) day(-1)) and combined treatment (I + Mel) group. Ten weeks later, the serum testosterone levels, intracavernosal pressure (ICP), mean arterial pressure (MAP), malondialdehyde (MDA), cyclic guanosine monophosphate (c-GMP), 8-hydroxydeoxyguanosine (8-OHdG), nitric oxide synthase (NOS), caspase-3 activity, sirtuin-1 and endothelial nitric oxide synthase (eNOS) protein expression and histological findings were assessed. The mean ICP/MAP ratio for the D group was lower than the mean ratios for the other groups. The treatment groups, particularly the I + Mel group, exhibited lower 8-OHdG and MDA levels and caspase-3 activity than the D group. The sirtuin-1 and eNOS expression and cavernosal tissue (CT) histology seemed to have been preserved by the melatonin and/or insulin therapy. These results were indicative of a profound protective effect of melatonin by the activation of sirtuin-1 protein expression against hyperglycemia-induced oxidative CT injury.
Keywords: antioxidant; erectile dysfunction; melatonin; sirtuin 1; streptozotocin; type 1 diabetes mellitus; NITRIC-OXIDE; PROTECTS; INJURY; DAMAGE; RESVERATROL; RELAXATION; MECHANISMS; MELLITUS; SIRT1